Implementasi Pembelajaran Abad 21 terhadap Hasil Belajar IPA Peserta Didik dengan Pengendalian Motivasi Belajar - Dian Meilani; Ummu Aiman (Universitas Pendidikan Indonesia (UPI), 2020)
Abstract Less optimal learning of science results in low learning outcomes of science. In overcoming this, it is necessary to apply variative learning in accordance with the demands of the current century, namely 21st century learning. The study aims to determine the effect of the implementation of 21st century learning on science learning outcomes in learners by controlling learning motivation. This research is experimental study. The study population was students of class V of SD Muhammadiyah 2 Kupang totaling 92 people and the sample used was 62 people, with a random sampling technique. Data were analyzed using one-way ANAVA test, ANAKOVA test, and product moment test. The instrument used in the form of science learning outcomes tests and questionnaires. The results showed that: 1) there was an effect of the implementation of 21st century learning on science learning outcomes with = 34.984 (0.05; 1:60) = 4.00. 2) There is an effect of the implementation of 21st century learning on science learning outcomes, after learning motivation is controlled by FA * = 36.106 (0.05; 1:59) = 4.00. 3) There is a significant contribution of learning motivation to the learning outcomes of science, by 66%. The implications of this study include: 1) educators play a more active and creative role in shaping 21st century learning in students by not only mastering science as a product, but especially as a process. 2) The implementation of 21st century learning requires patience, determination, creativity, innovation in designing learning so that students actually participate in learning so that the required skills are formed in accordance with the 21st century. 3) Adequate learning facilities to support learning so as to improve learning outcomes in a manner optimal. Abstrak Pembelajaran IPA yang kurang optimal mengakibatkan rendahnya hasil belajar IPA. Dalam mengatasi hal tersebut perlunya menerapkan pembelajaran variatif yang sesuai dengan tuntutan abad saat ini yaitu pembelajaran abad 21. Penelitian bertujuan untuk mengetahui pengaruh implementasi pembelajaran abad 21 terhadap hasil belajar IPA pada peserta didik dengan pengendalian motivasi belajar. Penelitaian ini merupakan penelitiankuantitatif berupa eksperimen. Populasi penelitian adalah peserta didik kelas V SD Muhammadiyah 2 Kupang berjumlah 92 orang dan sampel yang digunakan sebanyak 62 orang, dengan teknik pengambilan sampel random sampling. Data dianalisis menggunakan uji ANAVA satu jalur, uji ANAKOVA, dan Uji product moment. Instrument yang digunakan berupa tes hasil belajar IPA dan kuisioner. Hasil penelitian menunjukan bahwa: 1) terdapat pengaruh implementasi pembelajaran abad 21 terhadap hasil belajar IPA dengan = 34,984 (0,05; 1:60) = 4,00. 2) Terdapat pengaruh implementasi pembelajaran abad 21 terhadap hasil belajar IPA, setelah motivasi belajar dikendalikan dengan = 36.106 (0,05; 1:59) = 4,00. 3) Terdapat kontribusi signifikan motivasi belajar terhadap hasil belajar IPA, sebesar 66%. Implikasi penelitian ini diantaranya: 1) pendidik berperan lebih aktif dan kreatif membentuk pembelajaran abad 21 pada peserta didik dengan tidak hanya menguasai ilmu pengetahuan sebagi produk, tetapi terutama sebagai proses. 2) Implementasi pembelajaran abad 21 memerlukan kesabaran, tekad, kreatifitas, inovasi dalam merancang pembelajaran sehingga peserta didik benar-benar mengikuti pembelajaran sehingga terbentuk keterampilan yang dibutuhkan sesuai dengan abad 21. 3) Fasilitas belajar yang memadai guna menunjang pembelajaran sehingga dapat meningkatkan hasil belajar secara optimal.